Comparative Biophysical and Ultrastructural Analysis of Melanins Produced by Clinical Strains of Different Species From the Trichosporonaceae Family - de Andrade, Iara Bastos; Araújo, Glauber Ribeiro de Sousa; Brito-Santos, Fábio; Figueiredo-Carvalho, Maria Helena Galdino; Zancopé-Oliveira, Rosely Maria; Frases, Susana; Almeida-Paes, Rodrigo (Frontiers in Microbiology, 2022)
Melanin is one of the most studied virulence factors in pathogenic fungi. This pigment protects them from a series of both environmental and host stressors. Among basidiomycetes, Cryptococcus neoformans and Trichosporon asahii are known to produce melanin in the presence of phenolic precursors. Other species from the Trichosporonaceae family also produce this pigment, but the extent to this production among the clinically relevant species is unknown. For this reason, the aim of this study was to verify the production of melanin by different Trichosporonaceae species of clinical interest and to compare their pigments with the ones from C. neoformans and T. asahii, which are more prevalent in human infections. Melanin was produced in a minimal medium supplemented with 1 mM L-dihydroxyphenylalanine (L-DOPA). Pigment was evaluated using scanning electron microscopy, Zeta potential measurements, and energy-dispersive X-ray spectroscopy. It was found that, besides C. neoformans and T. asahii, Trichosporon japonicum, Apiotrichum montevideense, Trichosporon inkin, Trichosporon faecale, Cutaneotrichosporon debeurmannianum, and Cutaneotrichosporon arboriformis also produce melanin-like particles in the presence of L-DOPA. Melanin particles have negative charge and are smaller than original cells. Variations in color, fluorescence, and chemical composition was noticed between the studied strains. All melanins presented carbon, oxygen, sodium, and potassium in their composition. Melanins from the most pathogenic species also presented iron, zinc, and copper, which are important during parasitism. Biophysical properties of these melanins can confer to the Trichosporonaceae adaptive advantages to both parasitic and environmental conditions of fungal growth.